Vertebrate cells genetically deficient for Cdc14A or Cdc14B retain DNA damage checkpoint proficiency but are impaired in DNA repair - Mocciaro, Annamaria; Berdougo, Eli; Zeng, Kang; Black, Elizabeth; Vagnarelli, Paola; Earnshaw, William; Gillespie, David; Jallepalli, Prasad; Schiebel, Elmar (The journal of cell biology, 2010)
A recent study suggested that human Cdc14B phosphatase has a central function in the G2 DNA damage checkpoint. In this study, we show that chicken DT40, human HCT116, and human telomerase reverse transcription-immortalized retinal pigment epithelial cells deleted for the Cdc14A or Cdc14B gene are DNA damage checkpoint proficient and arrest efficiently in G2 in response to irradiation. Cdc14A knockout (KO) or Cdc14B-KO cells also maintain normal levels of Chk1 and Chk2 activation after irradiation. Surprisingly, however, irradiation-induced γ-H2A.X foci and DNA double-strand breaks persist longer in Cdc14A-KO or Cdc14B-KO cells than controls, suggesting that Cdc14 phosphatases are required for efficient DNA repair.
Gesehen am 27.04.2023